2017
DOI: 10.7863/ultra.16.05083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Normal Tonsils in Pediatric Patients With Ultrasonography

Abstract: The tonsils of almost all pediatric patients could be evaluated by ultrasound, particularly for patients older than 3 years. Additionally, a striated pattern of the tonsils was observed in most cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…This study was done to assess the possibility of using USG in measuring tonsil volume. In previous studies, USG was reported to be a useful imaging method in both the diagnosis and treatment of tonsillar diseases in pediatric populations . A study by Bandarkar et al reported the tonsil USG method in children and argued its inclusion within the routine algorithm, especially in peritonsillar abscess cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was done to assess the possibility of using USG in measuring tonsil volume. In previous studies, USG was reported to be a useful imaging method in both the diagnosis and treatment of tonsillar diseases in pediatric populations . A study by Bandarkar et al reported the tonsil USG method in children and argued its inclusion within the routine algorithm, especially in peritonsillar abscess cases.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Bandarkar et al reported the tonsil USG method in children and argued its inclusion within the routine algorithm, especially in peritonsillar abscess cases. A study by Hosokawa et al also reported that USG could be used to assess the tonsil tissue in almost all children with ease. In this study, we investigated the success of USG also in adults in addition to a pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ultrasound has been gaining favor due to its capacity to visualize the oropharynx with precision. 11,12,[26][27][28] One study in particular examined tonsil volumes of 26 children via ultrasound and reported good correlation of ultrasound and volumetric measurements. 12 However, our study is the first to confirm that tonsil size in all 3 dimensions is accurately measured with ultrasound and correlates with ex vivo specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The laterally located, triangular‐shaped sublingual glands are usually homogenous, symmetrical and relatively hyperechoic 14 . The lingual artery branches and the main duct draining the submandibular glands pass medially 11 …”
Section: Ultrasound Technique: Trans‐cervical and Intra‐oralmentioning
confidence: 99%
“…During the oral phase the tongue causes the posterior movement of the bolus. Lingual movement propels the bolus posteriorly, and the buccal musculature ensures the material does not fall into the lateral sulci 11 …”
Section: Introductionmentioning
confidence: 99%